Inovasi Pemasaran dan Pendampingan Penyusunan Laporan Keuangan Dengan Aplikasi “SI APIK” pada UMKM Roti Maryam “NULIN” - Pipin Fitriasari; Fara Annisa Syam; Siti Masyitah; Sofia Maulida (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity in the form of mentoring for MSMEs in Gunung Sari Ulu Village aims to provide understanding to MSME actors in Gunung Sari Ulu Village about the importance of brands and packaging in a product and the need for digital financial management and digital marketing (online). MSME mentoring activities are carried out to innovate Maryam bread products